Sokongan Sosial Sebagai Pengantara Pengaruh Optimistik Ke Atas Kebahagiaan Remaja Di Pengajian Tinggi (Social Support As A Mediator Of The Influence Of Optimism Towards Happiness Among Adolescents In Higher Education) - Mahirah Masdin; Balan Rathakrishnan; Getrude Cosmas (2018)
Happiness is the natural goal of life for every human being. Every indivdual is trying to find happiness because it describes a good life. Therefore, this study aims to examine an influence on happiness, which is optimistic, using a positive psychological strength,. Social support is utilized as an external quality as it supports the optimistic influence towards happiness. The study was conducted on 436 adolescents in higher education, aged between 18 and 25 years old. The quantitative study uses a set of questionnaires to obtain the data, Extended Life Orientation Test for optimistic measurements, Inventory of Socially Supportive Behavior Short Form measures social support, and Oxford Happiness Questionnaire measures adolescents happiness. Descriptively, adolescents in higher education showed high optimism (Min = 3.77, SP = .62), while moderate social support for the three forms of support, namely guidance support (Min = 3.07, SP = .81), emotional support (Min = 3.17, SP = .99) and tangible support (Min = 2.82, SP = .95). Adolescents in higher education reported having a moderate level of happiness (Min = 3.39, S.P = .92). The findings show that guidance and emotion support mediating the influence of optimistic towards happiness among adolescents in higher education. Tangible support does not play any role. The implication of the study is to adolescents that even the positive attitudes of optimistic can enhance their happiness, but the guidance and emotional support from significant people can further reinforce those influences.